Підвищення надійності і точності амплітудно-часових перетворювачів вбудованих мікроелектронних пристроїв - Лобур, М. В.; Іванців, Р. Д. (Видавництво Національного університету "Львівська політехніка", 2003)
Розглядається питання використання резервованої апаратури для одночас-ного підвищення надійності і точності роботи вимірювальних перетворювачів. Наведено декілька прикладів, в яких резервована апаратура використовується для підвищення точності вимірювань за рахунок просторового осереднення ряду результатів перетворень. Traditional reliability rise method is reserving of apparatus. Reserving can be "cold" or "hot". In both cases there must be an arbiter (device or operator), which determines a technical apparatus state, chooses a most workable channel out of the reserved ones and includes this channel. Such methodology of reliability rise produces the tangible results, but has some peculiarities. The intervention of arbiter is also necessary at faults, and there will be momentary function execution break with reserved device at reserve switching.